Differential Susceptibility to Infectious Respiratory Diseases between Males and Females Linked to Sex-Specific Innate Immune Inflammatory Response - Chamekh, Mustapha; Deny, Maud; Romano, Marta; Lefèvre, Nicolas; Corazza, Francis; Duchateau, Jean; Casimir, Georges (Frontiers in Immunology, 2017)
It is widely acknowledged that males and females exhibit contrasting degrees of susceptibility to infectious and non-infectious inflammatory diseases. This is particularly observed in respiratory diseases where human males are more likely to be affected by infection-induced acute inflammations compared to females. The type and magnitude of the innate immune inflammatory response play a cardinal role in this sex-bias. Animal models mimicking human respiratory diseases have been used to address the biological factors that could explain the distinct outcomes. In this review, we focus on our current knowledge about experimental studies investigating sex-specific differences in infection-induced respiratory diseases and we provide an update on the most important innate immune mechanisms that could explain sex-bias of the inflammatory response. We also discuss whether conclusions drawn from animal studies could be relevant to human.